Africasian Democracy: A Political Prescription for Good Governance in Nigeria (Global Journal of Human-Social Science, 2021)
The liberal democracy copied from the West is not working in Nigeria because of cultural and ethnic diversities as well as many other factors. The masses are ethnically disunited against themselves while the members of the predatory political class from different ethnic groups are united in sharing the national cake in what is known as elite conspiracy or club of capture. Using descriptive method of data analysis, some illiberal democratic traditions in Asia appear to have been strengthening developmental efforts in the continent while the liberal political system in Nigeria constitutes an impediment to economic growth and development. The Asian political system and the communal traditions in Africa can be blended to form africasian democracy and put into practice in Nigeria for sustainable development and good governance. To this end, it is recommended that in the next presidential election in Nigeria, a courageous candidate who can be violent in decision taking should be elected as president to dismantle the fallacious, elitist and wasteful system of government.
Keywords: democracy; africasian; volcanic; politics; machiavellian; predatory; elite